2020
DOI: 10.1140/epjp/s13360-020-00755-4
|View full text |Cite
|
Sign up to set email alerts
|

Charged strange star with Krori–Barua potential in f(R, T) gravity admitting Chaplygin equation of state

Abstract: In present paper a new compact star model in f (R, T ) gravity is obtained where R and T denote the Ricci scalar and the trace of energy-momentum tensor Tµν respectively. To develop the model we consider the spherically symmetric space-time along with anisotropic fluid distribution in presence of electric field with f (R, T ) = R + 2γT where γ is a small positive constant. We have used the Chaplygin equation of state to explore the stellar model. The field equations for f (R, T ) gravity have been solved by em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Faraoni [88] revisited the issue of the correct Lagrangian description of a perfect fluid L m = p versus L m = −ρ in relation with modified gravity theories in which galactic luminous matter couples nonminimally to the Ricci scalar and one concluded that the Lagrangians are only equivalent when the fluid couples minimally to gravity and not otherwise. Bhar [84] presented a spherically symmetric isotropic strange star model under the framework of f (R, T ) theory of gravity by assuming L m = ρ. For our present model the energy-momentum tensor is given by…”
Section: Einstein-maxwell Equation In F (R T ) Gravity and Conformal Symmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Faraoni [88] revisited the issue of the correct Lagrangian description of a perfect fluid L m = p versus L m = −ρ in relation with modified gravity theories in which galactic luminous matter couples nonminimally to the Ricci scalar and one concluded that the Lagrangians are only equivalent when the fluid couples minimally to gravity and not otherwise. Bhar [84] presented a spherically symmetric isotropic strange star model under the framework of f (R, T ) theory of gravity by assuming L m = ρ. For our present model the energy-momentum tensor is given by…”
Section: Einstein-maxwell Equation In F (R T ) Gravity and Conformal Symmetrymentioning
confidence: 99%
“…by taking p r = p t = p in Ref. [84]. Here E(r ) represents the electric field of the charged fluid sphere.…”
Section: Einstein-maxwell Equation In F (R T ) Gravity and Conformal Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Zubair et al [27] obtained anisotropic compact star models in f (T ) gravity with Tolman-Kuchowicz spacetime. Bhar [28] explored a charged model of compact star in f (R, T ) gravity admitting chaplygin equation of state. Rej and Bhar [29] obtained charged strange star in f (R, T ) gravity with linear equation of state.…”
Section: Introductionmentioning
confidence: 99%
“…Heintzmann and Hillebrandt [11] showed through a model of relativistic neutron stars at high densities that while the maximum mass for compact stars is limited to 3-4 𝑀 , there is no limited mass for arbitrarily large anisotropy measurements.In recent years, many physicists have studied the effect of anisotropy of matter in compact stars, taking the radial component of pressure is different from tangential component of pressure in compact stars [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Attempts have also been made to model both charged and uncharged compact star models using the modified theories of gravity [32,33,34,35]. In the study of anisotropic stars, there are two components of pressure, namely, radial pressure 𝑝 𝑟 and tangential pressure 𝑝 𝑡 .…”
Section: Introductionmentioning
confidence: 99%